Improvement in the detection rate of t(14;18) translocation on paraffin-embedded tissue: a combination approach using PCR and FISH - Shaminie, J.; Peh, S.C.; Tan, J.A.M.A. (2003)
Aims: PCR has been the primary method used for the detection of t(14;18) translocation in formalin-fixed, paraffin-embedded tissues. This technique mainly targets the well-characterised breakpoint regions in chromosomes 14 and 18. FISH is now applicable on paraffin tissue sections and has been suggested to be capable of detecting essentially 100 of t(14;18) translocated cases. In this study, we described the application of both PCR and FISH for the detection of t(14;18) translocation. Methods: Fifty follicular lymphoma cases were retrieved from the files of the Department of Pathology, University of Malaya Medical Centre (UMMC). Nested PCR amplification of MBR/JH and mcr/JH was performed in these cases, and those cases that did not demonstrate the translocation were subjected to FISH analysis. Results: Thirty cases (60) had t(14;18) translocation detected by PCR, 25 (50) had breakpoint with MBR and five (10) involved mcr. Twenty cases without detectable t(14;18) translocation by PCR were analysed by FISH. Eleven cases were successfully probed, and four of them showed positive translocation signal. Conclusions: The combination of PCR and FISH analysis on paraffin tissue sections for the detection of t(14;18) translocation increases the sensitivity of detection from 60 to 68. Problems encountered in our FISH analysis on tissue sections impose certain limitations in using this technique for retrospective screening of large number of samples. Therefore, we suggested the application of PCR as the first screening tool on retrospective archival materials, followed by FISH on those PCR-negative cases.